Students’ flexible learning context and preferences during the COVID-19 pandemic in Albay, Philippines - Bercasio, Rebecca Rosario Orona; Dugan, Marinel Agustin (Intelektual Pustaka Media Utama, 2025)
The COVID-19 pandemic has significantly disrupted education worldwide and schools used flexible learning as an alternative modality. This study used a quantitative approach and descriptive research to describe the learning context and determine the students’ preferences in learning modalities, learning materials, learning tasks, and assessment techniques for flexible learning. Four hundred thirty-four (434) students from different levels in Bicol, Philippines, responded to the online survey questionnaire. The results reveal that the learners’ context is inconducive for flexible learning as most do not have learning spaces and experience power interruptions and Internet disconnections. The students were provided individual or group learning tasks and experienced self-paced and interactive learning in flexible learning classes. The students reported that their learning materials, learning tasks, and assessment techniques in flexible learning include teacher-made learning resources, preference for affordable and convenient devices and applications, and usage of e-classroom or online platforms for major assessments with returned scores and feedback. Describing and identifying flexible learning conditions and students’ needs were essential in creating school or community initiatives to enhance students’ flexible learning experiences. The proposed initiatives can be used as strategies for future circumstances that will need flexible learning implementation.